Comparative evaluation of marginal fit accuracy of two different designs of endocrown manufactured through CAD-CAM system: An in vitro study - Khushbu Rakesh Gupta; Deepesh Kumar Gupta; Anumeha Jha; Shivam B. Shukla; Aayush Mukund Dubey (The Journal of Indian Prosthodontic Society)
Aims: To compare the accuracy of marginal fit of CAD-CAM endocrown with two different preparation forms, i.e., endocrown with ferrule and endocrown without ferrule. Settings and Design: Various studies have opined on the impact of preparation form on the marginal fit of endocrown, but studies on the effect on the marginal fit of digitally milled endocrown with and without ferrule are sparse. Materials and Methods: Total of 30 typodont were sectioned 3 mm above the cemento-enamel junction, and central cavity was prepared to depict a severely destructed tooth. The typodonts were divided into two groups: Group 1 contained specimens for endocrown without ferrule (WoF); Group 2 contained specimens for endocrown with ferrule (WF). The typodonts were prepared based on standard preparation. The specimens were then scanned using intraoral scanner, and the stereolithography (STL) was generated. Endocrowns were designed in the Exocad software using a digital library. The STL file format is translated into millable data file format (CNC- Computer numerical control) in the inLAB MC X5 Milling machine. The marginal fit of endocrowns was then assessed in the stereomicroscope. Statistical Analysis: The data was analysed with a digital image analyser. The result was generated using a two-way ANOVA test. The significance level was set at P ≤ 0.05. Results: In the present study, the marginal fit of WoF showed a superior marginal fit than WF. A statistically significant difference was seen in the marginal fit of two endocrowns, with a higher marginal discrepancy observed in the endocrown with the ferrule. The P value for the difference in the means of the marginal gap without and with ferrule (-13.42) is zero. Maximum marginal gap of 96 micron is observed for with ferrule (WF) design at location B. Minimum marginal gap of 29 micron is observed for without ferrule (WoF) at location D. Conclusions: Endocrown without a ferrule can provide a better marginal fit and can contribute to the long-term survival of restoration.